The effectiveness of PERMA model education on university students' well-being - Sanaz Dorri Sedeh; Asghar Aghaei (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Approximately 46% of university students experience mental health problems. Additionally, the university students' well-being was lower than their general well-being. This study was conducted to investigate the effectiveness of the PERMA model education on university students' well-being. MATERIALS AND METHODS: This study used a semi-experimental research design, involving one intervention group and one control group. The groups underwent a pre-test, post-test, and a 45-day follow-up. This study was conducted at the Department of Education and Psychology, Azad University of Isfahan (Khorasgan) Branch, and all students in this department were considered the statistical population for this study. The research tools used were the Butler and Kern PERMA-Profiler questionnaires. In two stages, pre-test, post-test, and follow-up, the experimental group participated in six educational intervention sessions. Educational interventions included Seligman's PERMA model, which defines psychological well-being in five domains: positive emotions (P), engagement (E), relationships (R), meaning (M), and accomplishment (A). Each session lasted for 90 min over 3 weeks (two sessions per week), while the control group had no training sessions. RESULTS: Multiple covariance analysis of well-being showed no significant difference found between the two groups in the pre-test (P = 0.19). However, a significant improvement was observed in the intervention group in the post-test (P = 0.03) and follow-up (P = 0.001). CONCLUSION: This study suggests the use of Seligman's PERMA model to improve the psychological well-being of university students. It is recommended that the educational system use this model to help university students improve their mental health, enhance their life satisfaction, and prevent mental illnesses such as depression and stress.